2022
DOI: 10.1007/s40596-022-01674-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Iranian Psychiatric Trainees’ and Early Career Psychiatrists’ Well-being, Work Conditions, and Education

Abstract: Objectives This study was conducted to investigate the impact of the COVID-19 pandemic on psychiatric trainees and early career psychiatrists in Iran. Methods In this cross-sectional survey, the authors used a 24-item questionnaire inquiring about the sociodemographic characteristics of the participants, their views on the impact of the COVID-19 pandemic on their professional careers, methods of education, workplace environment, well-being and mental health, and the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A mixed-methods study will be conducted to investigate the impact of the COVID-19 pandemic on ECPs in three countries of the EMRO, a sub-community of WHO that comprises a group of developing countries with diverse economies located in Southwest Asia, Western Asia, and North Africa ( 11 ). This study will focus on three EMRO member countries: Tunisia, a North African nation with a lower-middle-income ( 12 ); Egypt, a country with a medium level of development with its Human Development Index (HDI) ranking of 101 out of 169 nations by the World Bank ( 13 ); and Iran, where the promotion of mental health and occupational mental health is often overlooked in psychiatry training programs ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…A mixed-methods study will be conducted to investigate the impact of the COVID-19 pandemic on ECPs in three countries of the EMRO, a sub-community of WHO that comprises a group of developing countries with diverse economies located in Southwest Asia, Western Asia, and North Africa ( 11 ). This study will focus on three EMRO member countries: Tunisia, a North African nation with a lower-middle-income ( 12 ); Egypt, a country with a medium level of development with its Human Development Index (HDI) ranking of 101 out of 169 nations by the World Bank ( 13 ); and Iran, where the promotion of mental health and occupational mental health is often overlooked in psychiatry training programs ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Questions 1-8 included demographic items (e. g. age, gender, area of work). We measured mental strain with 20 items on subjective burden (e. g. workload, loss of free time, sleeping disorder, worries about the future; Q9, 10, 12, 24, 25, 26, 30, 33), worries about the virus (Q27, 28, 29), measures and management by political leaders and hospital management (Q11, 13,14,19,20,21,22) and the treatment of both patients tested positive and negative for COVID-19 (Q31, 32). The items were rated on a five-point-Likert-scale from 1 ("strongly disagree") to 5 ("strongly agree").…”
Section: Questionnairementioning
confidence: 99%
“…One study conducted among a sample of 460 PHCWs in the USA revealed that 73 % of workers reported moderate to high levels of role stress and 56 % reported moderate to high levels of emotional exhaustion [8]. In view of the pandemic , there are numerous studies on mental health among other HCWs (OHCWs) not working in psychiatric hospitals [9,10], but only few on PHCWs' mental health [11][12][13][14][15][16][17]. Among the existing studies, the majority assessed working conditions, general well-being or prevalence of depression, anxiety, stress and burnout in sam-ples exclusively consisting of psychiatrists or PHCWs [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global death amounted to 6.9 million, accounting for 0.08% of the global population ( 1 ). The COVID-19 pandemic has far-reaching impacts on various societal sectors, generates considerable stress among healthcare workers ( 2 , 3 ), and induces significant emotional strain on the general population due to the extensive infection rates and associated mortality ( 4 6 ). This considerable burden leads to psychological and mental health problems, emanating not only from the physical symptoms of the disease but also from various stressors ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%